Longevity of different in-office treatments for dentin hypersensitivity: A 6-month randomized and parallel clinical trial - Fernanda de Souza e Silva Ramos; André Luiz Fraga Briso; Érika Mayumi Omoto; Edgar Dutra Zanotto; Paulo Henrique dos Santos; Bruna Perazza; Ticiane Cestari Fagundes (PLoS ONE, 2026)
This longitudinal, randomized, parallel-design clinical trial aimed to evaluate the long-term effectiveness of different in-office treatments for dentin hypersensitivity (DH) over a 6-month period. A total of 192 teeth presenting DH associated with root surface exposure were treated with one of four desensitizing agents: fluoride varnish (Duraphat – FLU, active control), bioactive ceramic solution (Biosilicate – BIOS), universal self-etching adhesive (Single Bond Universal – SBU), and a bioactive, photoactivated varnish containing PRG fillers (SPRG). DH was assessed using a visual analogue scale (VAS) to analyse intensity of sensitivity and a computerized visual scale (CoVAS) to observe the time course of sensibility at baseline, 7, 15, 30 days and 6 months post-treatment. Comparisons between groups were conducted using Fisher’s exact test for qualitative variables and analysis of variance (ANOVA) for quantitative variables. Longitudinal outcomes (VAS and CoVAS) were evaluated using linear mixed-effects models, with post hoc comparisons performed using orthogonal contrasts. Statistical differences were found for VAS analysis (p < 0.05). Comparing the desensitizers, FLU showed higher sensitivity than SBU, after 7 days. Comparing follow-up periods, a significant reduction in DH beginning at 7 days for BIOS and SBU, and at 15 days for FLU and SPRG. Regarding CoVAS time course, FLU exhibited a significantly shorter time course than SBU, after 15 days and 6 months of follow-up (p ≤ 0.05). SPRG was the only treatment that showed no difference in reaction time between 6 months and baseline (p > 0.05). In conclusion, root exposure height and the presence of an antagonist tooth may influence the initial intensity of DH. All treatments reduced DH over 6 months. Only bioactive resin varnish maintained the same reaction time in all periods. Universal adhesive system had slowed pain reaction time compared to conventional fluoride varnish.